History of the Serang Regent’s Office its Role as the Center of Colonial Goverment in Serang Regency in 1829-1945 - Issyatunnajia, Issyatunnajia; Fadillah, Moh. Ali; Ribawati, Eko (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2026)
This research aims to determine the history of the Serang Regent's Office and its role as the Center of Colonial Government in Serang Regency in 1829-1945. The method used in this research is historical research methods assisted by the theory of cultural heritage, colonization and the emergence of colonial cities. The research results show that the Serang Regent's office was completed in 1826 and began to be actively used as the Serang Regent's office in 1829, a year after the government center moved from Kaibon to the Serang area. This development was motivated by the ineffectiveness of the central government in Kaibon and the lack of adequate government offices at that time. From the start, this building was designed as an office and official residence for the Serang regents who served and was used as the center of colonial government activities, as well as the center of community activities in various aspects of life, both religious life, social life and culture.